Internationalising the currency while leveraging massively: The case of China - Alicia García-Herrero (Bruegel, 2015)
This paper reviews the steps that China has taken towards financial reform with a particular focus on capital account liberalisation and internationalisation of the use of the renminbi. After a slowdown in reform momentum during the global financial crisis, there is a clear push towards reform, especially in terms of RMB internationalisation. During the same period, though, China's debt has doubled, reaching levels that are clearly above those of most emerging markets. This increases the risks embedded in financial reform and, in particular, capital account liberalisation. At this juncture, however, China has no option but to press for reform since the current growth model is no longer working and China urgently needs to better allocate its savings.
Keywords: G15; G18; E44; E58; F31; F32; 330; China; RMB internationalisation; Yuan; Capital Account Convertibility; Financial Reform; Debt; Leveraging